Highlighting of ferromagnetism above room temperature in Cd-doped ZnO thin films grown by MOCVD. (September 2015) - Souissi, M.; Fouzri, A.; Schmerber, G.
Abstract: In this letter, we report a successful growth of Cd-doped ZnO (ZnO: Cd) thin films on c-plane sapphire substrate by metal–organic chemical vapor deposition (MOCVD) technique at 380 °C. We have used Dimethyl-Cadmium (DMCd) to intentionally incorporate cadmium (Cd) during the crystal growth of ZnO. X-ray diffraction measurements revealed that the samples were crystalline in agreement with wurtzite structure and no metallic Cd or other secondary phases were detected. Scanning electron microscopy images showed facetted grains for the films. Hysteresis loops, zero-field cooling and field cooling curves demonstrated the ferromagnetic properties of the ZnO: Cd thin films, which makes them potentially useful as building components for spintronics. The Curie temperature of the ZnO: Cd was estimated to be above 350 K. Highlights: The origin of the ferromagnetism in transition metal doped ZnO is not yet fully understood. Cd-doped ZnO have been grown by MOCVD. Ferromagnetic behavior above room temperature for Cd-doped ZnO (ZnO: Cd) layers are observed.